Michel Ferlus (1935-2024) - Jean Pacquement (Moussons)
This text about Michel Ferlus, who passed away in March 2024, recalls his first linguistic explorations in Laos in the 1960s and his work as a researcher at the Centre national de la recherche scientifique on the languages of peninsular Southeast Asia.